Agrotourism as a Pillar of Sustainable Development: Systematic Literature Review - Hendrita, Juli; Frinaldi, Aldri; Lanin, Dasman; Rembrandt, Rembrandt; Umar, Genius; Aprilliani, Cici; Amelia, Kiki; Batubara, Fanny Yuliana; Hatika, Rindi Genesa; Febrina, Cory; Yasril, Abdi Iswahyudi (Science and Environmental Journal for Postgraduate, 2025)
Agrotourism is a series of tourism activities that utilize agricultural potential as tourist attractions that can be enjoyed through natural scenery, plant and animal conservation, educational activities in agricultural and plantation areas that have a diversity of production activities and technologies, and can also promote community culture. Agrotourism potential can be developed through integrated agriculture such as farming, animal husbandry, and educational tourism. This study aims to identify the development of research related to the sustainability of agrotourism conducted worldwide through data obtained from relevant journals for the period 2000 to 2025. There are 58 studies related to the sustainability of agrotourism. The method used in this study is the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate, and interpret all available research in fields and topics related to relevant and specific research questions. Using the SLR method, systematic reviews and journal identification can be carried out, with each process following predetermined steps or protocols. The results of this study show that agrotourism research has shown consistent growth from 2000 to 2025, with a significant surge in 2024, indicating the importance of agrotourism in sustainable tourism. The country conducting the most research in the field of agrotourism sustainability is Indonesia, with research based on the number of citations each year 2000 to 2025 being 4 out of 20 studies.